2013
DOI: 10.1038/jid.2013.234
|View full text |Cite
|
Sign up to set email alerts
|

Premature Termination Codon Read-Through in the ABCC6 Gene: Potential Treatment for Pseudoxanthoma Elasticum

Abstract: Pseudoxanthoma elasticum (PXE) is an autosomal recessive disorder manifesting with ectopic connective tissue mineralization, caused by mutations in the ABCC6 gene, ~35% of all mutations being premature termination mutations. In this study, we investigated the therapeutic potential of the nonsense codon read-through-inducing drug, PTC124, in treating PXE. The ability of this drug to facilitate read-through of nonsense mutations was examined in HEK293 cells transfected with human ABCC6 expression constructs harb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 26 publications
1
40
0
2
Order By: Relevance
“…Multiple experimental approaches with cell lines, patient cells, animal models, and genetic disorder patients have demonstrated that the drug ataluren can restore expression to genes and mRNAs otherwise inactive because of the presence of premature nonsense codons (1,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)23). Collectively, such experiments have strongly suggested that ataluren promotes nonsense suppression, i.e., the insertion of near-cognate tRNAs at PTCs, but direct evidence for this activity has been lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple experimental approaches with cell lines, patient cells, animal models, and genetic disorder patients have demonstrated that the drug ataluren can restore expression to genes and mRNAs otherwise inactive because of the presence of premature nonsense codons (1,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)23). Collectively, such experiments have strongly suggested that ataluren promotes nonsense suppression, i.e., the insertion of near-cognate tRNAs at PTCs, but direct evidence for this activity has been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…1 and SI Appendix, Fig. S3) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)23); (ii) the effects on luciferase activity could not be independently replicated by others (24) or by us (SI Appendix , Fig. S3C); (iii) ataluren's putative luciferase inhibitory activity depends on a specific enzyme substrate (25); and (iv) most of the hypothetical inhibitory molecule, PTC124-AMP (22), is rapidly converted to the active readthrough molecule PTC124 (ataluren) under conditions of in vitro translation (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mineralizasyonun önüne geçmek için diyette magnezyumu arttırmak üzerine deneyler yapılmaktadır, faydalı olduğuna dair yayınlar mevcuttur (11). ABCC6 geninde PTC124 aracılığıyla saçma mutasyonların oluşturulmasını tedavi için öneren çalışmalar bulunmaktadır (14). Moleküler genetik çalışmalar devam etmektedir (8,13 …”
Section: Discussionunclassified
“…Some of these approaches could be adopted from the progress made in other heritable diseases, including those being developed for other ABC transporter gene defects such as cystic fibrosis. Examples of such approaches include development of small molecules that facilitate the readthrough of premature termination codon-causing mutations, so as to allow synthesis of the full-length protein from the mutant allele [81]. In case of PXE, approximately 30-35% of all mutations are premature termination-causing mutations in the ABCC6 gene, including the most common recurrent mutation p.R1141*, which accounts for approximately 25% of all mutations in caucasian patient populations [11].…”
Section: Development Of Molecular Therapiesmentioning
confidence: 99%